PEGARUH PARTISIPASI PENGGUNA DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Kurniasari, Novelya Riyanti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to examine the influence of usersâ participation in the development of information system and top management support to the performance of the accounting information system on state banks in Sidoarjo. The population are all state bank employees in Sidoarjo. The samples have been chosen by using purposive sampling method which is based on certain criteria. The analysis technique is using multiple linear regressions. Based on the result of the calculation it can be concluded that the determination coefficient value R2 (R Square) that is 0.537 shows that the budgeting participation and top management support are capable to explain the AIS performance approximately 53.7%, while the remaining is 46.3% which is explained by other variables outside this research. While based on the hypothesis test it is found that the participation of users in the development of information system, when the participation of the users in the development of accounting information system is greater, the performance of accounting information system will improve. The support level which is provided by the top management for the organization information system has an influence to the accounting information system of State banks in Sidoarjo. The support level which is provided by top management can be a very important factor in determining the successful of all activities which are related to information system.Keywords : Usersâ Participation in the Development of Information System, Top Management Support, the Performance of the Accounting Information System.